Microbial diversity and composition in the gut microbiome of patients during systemic inflammatory response syndrome: can we use gut bacteria as potential biomarkers to characterize sepsis? - Rafaela Ramalho Guerra; Rafaela Ramalho Guerra; Rafaela Ramalho Guerra; Patricia da Silva Fernandes; Otávio von Ameln Lovison; Otávio von Ameln Lovison; Giovanna de Ross Forni; Giovanna de Ross Forni; Gabriel Silva de Oliveira; Luana Cristina Viana; Dariane Castro Pereira; William Latosinski Matos; et al. (Frontiers in Cellular and Infection Microbiology)
BackgroundCritically ill patients, including those with systemic inflammatory response syndrome (SIRS) and sepsis, frequently exhibit gut microbiota disruption due to physiological stress and broad-spectrum antimicrobial therapy (AT). Although antibiotics are essential for controlling infection, they can destabilize the gut microbiota and may contribute to poorer clinical outcomes. The characterization of the gut microbiota of these patients may inform microbiota-based interventions to mitigate antibiotic-induced dysbiosis.ObjectiveThis study aimed to identify key bacterial taxa that distinguish sepsis from non-sepsis patients.MethodsA total of 89 stool samples (51 non-sepsis, 38 sepsis) were evaluated by amplicon sequencing the 16S rRNA gene to assess microbiota diversity and differential abundance. Samples were stratified by antibiotic exposure time: early AT (within 5th days of initiation) and prolonged AT (6th to 10th days). Additionally, patients were also grouped based on their AT: beta-lactam combined with other antimicrobial classes (BL-combined) and beta-lactam monotherapy (BL).ResultsDuring early AT, alpha diversity (Shannon index) was significantly lower in sepsis patients compared to non-sepsis patients (2.48 vs. 3.0, p = 0.01), whereas no significant difference was observed after prolonged treatment (2.65 vs. 2.89, p = 0.58). Beta diversity analysis (Aitchison distance) revealed significant differences between groups early AT (PERMANOVA, p = 0.005), but not in the later phase (p = 0.54), suggesting that microbial communities converge over time. Early AT taxonomic profiling showed a decrease in Anaerobutyricum spp. and an increase in Holdemania spp. in the sepsis group. In the non-sepsis group, Veillonella spp. was impacted by time and beta-lactam combination. Turicibacter spp. showed a reduction in the prolonged AT sepsis group, while Klebsiella spp. was more abundant in the BL-combined sepsis patients.ConclusionsSepsis and non-sepsis patients showed distinct gut microbiota profiles in early AT. In sepsis, the loss of taxa involved in key metabolic functions, as short-chain fatty acid production, reflects dysbiosis and may contribute to worse outcomes. Prolonged antibiotic use may favor enteropathogen overgrowth and gut translocation. These findings highlight the potential of microbiota-based strategies to guide antimicrobial therapy and improve clinical outcomes in critically ill patients.